Analysis of carbon fiber reinforced with resin epoxy using FEM analysis. (2021) - Kishore, Chandra; Bhatt, Vinayak; Jaiswal, Ritik; Jugran, Shivam; Rawat, Dipak; Verma, Deepak
Abstract: Application of CFRP has been increased from the past as they offer much enhanced properties with less weight as compared to traditional metal such as cast iron. This development is the new spear head of the material technology due to its incomparable potential. This paper investigate the variation in the properties of CFRP with the variation in the Fiber mass percentage. ASTM standard test specimen are utilized and test is carried out with the help of Ansys Academic software. The primary objective of this paper is to evaluate equivalent stress, strain and total deformation of the composite under same load.